New Oriental genera in the family Issidae (Hemiptera: Fulgoromorpha) - Wang, Menglin; Bourgoin, Thierry; Zhang, Yalin (Zootaxa, 2017)
Three new Oriental Issidae genera and two new species identified by a previous molecular phylogeny analysis are described. Two new genera belong to the tribe Kodaianellini: Kodaianellissus gen. nov., type species: K. intorqueus sp. nov. from China and Tetricissus gen. nov., type species: T. philo (Fennah, 1978) from Vietnam. Another new genus representing Sarimini: Longieusarima gen. nov., type species: L. lunulia sp. nov. is described from China.